Federici, E., Santaemilia, J. (Eds.). (2022). New Perspectives on Gender and Translation: New Voices for Transnational Dialogues. Routledge. (pp. 204) https://doi.org/10.4324/9780429352287 - Huang, Qin; Liu, Qianru (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
Book review